Analisis dan Perancangan Alat Biogas Sebagai Energi Alternatif Skala Rumah Tangga Dalam Pemanfaatan Limbah Kotoran Sapi - Arifin, Jainal; Herlina, Firda; Amin, Ahmadil; Iman, Hendi Cahya (Proklamasi 45 University, 2023)
Energy in recent years has become a critical problem in the world. The increasing demand for energy due to population growth and depleted reserves is the problem of World Oil and Emissions. Fossil fuels bring pressure on every country to produce and use renewable energy. In addition, world oil prices have risen to 100 per barrel, which is also a serious cause that affects many countries' people. countries in the world, especially Indonesia. The method that needs to be used to improve the scarcity of Lpiji gas in Ambawang Village, Batu Ampar District is by using cow dung to become biogas. The stages are: Designing a household-scale biogas appliance, preparing materials and equipment, and testing the household-scale biogas appliance that has been designed. So it can reduce the scarcity of Lpiji gas. Based on observations in the Ambawang Village area, Batu Ampar District, they admitted that obtaining LPG fermented by anaerobic bacteria was difficult. The largest change in manometer air height occurred on days 19 and 30 in Variation S1, the change in manometer air height was 4 cm compared to the previous day. The total height of the manometer for 30 days was 28.2 cm. The pressure of biogas produced for 30 days was 104090.4 N/m2, the maximum amount of biogas evolution on days 19 and 30 was 0.4192011 m3, and the total amount of biogas for 30 days was 12.15 m3. The methane gas produced during 30 days of fermentation can be used on the stove for 51 minutes 34 seconds, and the color of the flame is slightly bluish, indicating that the methane gas produced still contains a small percentage of water. And can heat 1.5 liters of 93°C water for 12 minutes.